(untitled) (Research, Society and Development, 2022)
Access to education is established in the Constitution of the Federative Republic of Brazil, of 1988, as a right for all and a duty of the State and the family. However, even though this right is guaranteed in constitutional terms, the tools for its implementation deserve attention, notably with regard to social subjective specifics. In the meantime, the objective is to reflect on the technological possibilities of assistance in health education for deaf youth, in an integrated perspective, considering the barriers inherent to this public. The methodology was qualitative in nature, based on the method of literature review with the contribution of bibliographic and exploratory research, and for the analysis of information extracted from readings carried out in articles that discussed the topic in question. Support was sought for the content analysis method. Certainly, it appears that the management of technologies dynamizes and helps the teaching-learning process, whose premise lies in improving educational development, reducing and eliminating obstacles for students with disabilities.